The teacher training supported on virtual learning environment: swot application technique - Pilar COLÁS BRAVO; Juan DE PABLOS PONS (Ediciones Universidad de Salamanca, 2016)
This article approaches a model of teacher training supported on the TICs potential as a virtual learning environment which makes interactive communication and center formation possible. This contribution specializes on the pedagogical use of the TICS for teacher training based on the model of center formation, cooperative learning, and on-line learning from a sociocultural perspective. This training model starts in the virtual creation of cooperative learning teaching communities as a base for the permanent teacher training. The  SWOT technique is shown and developed as a methodology for the planning, creation and on-line dynamism of techers' nets. These nets have as an objective to establish cooperative learning communities for the continuous training of teachers and the educational innovation in centers.